Problematika Pembelajaran Karakter bagi Siswa Madrasah Ibtidaiyah 04 Blimbing Kecamatan Paciran Kabupaten Lamongan - Ridho, Muhammad Dhiyaur; Istikomah, Istikomah (MODELING: Jurnal Program Studi PGMI, 2023)
Character education is a planned process in shaping, directing and guiding student behavior in everyday life. The purpose of this study is to find out the problems of character learning by teachers to students at Madrasah Ibtidaiyah 04 Belimbing. This type of research is descriptive qualitative. Data sources are primary and secondary data. Data collection techniques used observation, interviews and documentation while data analysis techniques used data reduction, data presentation and drawing conclusions. The results of this study the teacher in planning character education emphasizes more on Islamic character education including character, honest character, disciplined character, environmental care character, responsible character and polite character and teachers have many problems in forming character education and teachers always try to shape character for students at Madrasah Ibtidaiyah 04 Belimbing include students who have not memorized prayer lessons, students often cheat. there are students who come late to school, students who litter, students who don't do homework and there are still students who use impolite language.